Auctions vs. negotiations in vertically related markets - Emanuele Bacchiega; Olivier Bonroy; Emmanuel Petrakis (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
In a two-tier industry with bottleneck upstream and two downstream firms producing vertically differentiated goods, we identify conditions under which the upstream supplier chooses exclusive or non-exclusive negotiations, or an English auction to sell its essential input. Auctioning off a two-part tariff contract is optimal for the supplier when its bar- gaining power is low and the final goods are not too differentiated. Otherwise, the supplier enters into exclusive or non-exclusive negotiations with the downstream firm(s). Finally, in contrast to previous findings, an auction is never welfare superior to negotiations.
Keywords: D43; L13; L14; 330; Vertical relationships; exclusive vs. non-exclusive relationships; auctions